Tuning the Cellular Uptake Properties of Luminescent Heterobimetallic Iridium(III)–Ruthenium(II) DNA Imaging Probes. Issue 43 (10th September 2014) - Wragg, Ashley; Gill, Martin R.; Turton, David; Adams, Harry; Roseveare, Thomas M.; Smythe, Carl; Su, Xiaodi; Thomas, Jim A.
Abstract: The synthesis of two new luminescent dinuclear Ir III –Ru II complexes containing tetrapyrido[3, 2‐a:2′, 3′‐c:3′′, 2′′‐h:2′′′, 3′′′‐j]phenazine (tpphz) as the bridging ligand is reported. Unlike many other complexes incorporating cyclometalated Ir III moieties, these complexes display good water solubility, allowing the first cell‐based study on Ir III –Ru II bioprobes to be carried out. Photophysical studies indicate that emission from each complex is from a Ru II excited state and both complexes display significant in vitro DNA‐binding affinities. Cellular studies show that each complex is rapidly internalised by HeLa cells, in which they function as luminescent nuclear DNA‐imaging agents for confocal microscopy. Furthermore, the uptake and nuclear targeting properties of the complex incorporating cyclometalating 2‐(4‐fluorophenyl)pyridine ligands around its Ir III centre is enhanced in comparison to the non‐fluorinated analogue, indicating that fluorination may provide a route to promote cell uptake of transition‐metal bioprobes. Abstract : Taking the nuclear option : The cellular uptake and nuclear targeting of luminescent heterodinuclear iridium–ruthenium complexes are potentiated through the incorporation of fluorinated ancillary ligands (see scheme).